How financial performance of world's top companies are related to business environment?. Issue 60 (25th December 2020) - Khazaei, Mehdi; Azizi, Mohammad
ABSTRACT: Businesses need an environment in which business conditions in features such as starting a business, registering property, getting credit, paying taxes, trading across borders and enforcing contract be simple. Every year, the world bank publishes a report on the business environment of different countries around the world with the aim of improving doing business environmental conditions. The purpose of the present study is to investigate the relationship between the financial performance of world's top companies and the business environment indicators. For this purpose, 176 top companies in the world from 2013 to 2018 that were profitable were selected as the statistical population. Doing business annual reports, and Fortune site were used to collect the data. Also the data analysis was done according to the panel data method using Eviews10 software. The results shows that there is a positive relationship between business environment Indicator and financial performance of world's top companies. On the other hand, the per capita income of the countries in which the top companies belonged was considered as a control variable and the results show that the per capita income has a positive and significant relationship with the financial performance of the top companies in the world.